2011
DOI: 10.1371/journal.pgen.1002186
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Araucan and Caupolican Integrate Intrinsic and Signalling Inputs for the Acquisition by Muscle Progenitors of the Lateral Transverse Fate

Abstract: A central issue of myogenesis is the acquisition of identity by individual muscles. In Drosophila, at the time muscle progenitors are singled out, they already express unique combinations of muscle identity genes. This muscle code results from the integration of positional and temporal signalling inputs. Here we identify, by means of loss-of-function and ectopic expression approaches, the Iroquois Complex homeobox genes araucan and caupolican as novel muscle identity genes that confer lateral transverse muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…Along with Mid, the Ara/Caup (Carrasco-Rando et al 2011), Ap (Bourgouin et al 1992), Msh (Nose et al 1998), Lms (Muller et al 2010), and Kr (Ruiz-Gomez et al 1997) transcription factors contribute to the development of LT3 and LT4. Ara/Caup is expressed in the progenitors for all four LTs, where it represses the VA1/2 fate and corresponding Slou expression in the LT3/4 progenitor (Carrasco-Rando et al 2011). These findings suggest that Ara/Caup acts at an early stage before the progenitor becomes fully committed to one developmental program.…”
Section: Transcriptional Network For Specification Of Lt3 and Lt4mentioning
confidence: 73%
See 3 more Smart Citations
“…Along with Mid, the Ara/Caup (Carrasco-Rando et al 2011), Ap (Bourgouin et al 1992), Msh (Nose et al 1998), Lms (Muller et al 2010), and Kr (Ruiz-Gomez et al 1997) transcription factors contribute to the development of LT3 and LT4. Ara/Caup is expressed in the progenitors for all four LTs, where it represses the VA1/2 fate and corresponding Slou expression in the LT3/4 progenitor (Carrasco-Rando et al 2011). These findings suggest that Ara/Caup acts at an early stage before the progenitor becomes fully committed to one developmental program.…”
Section: Transcriptional Network For Specification Of Lt3 and Lt4mentioning
confidence: 73%
“…At stage 10, we found that Mid was coexpressed with Kr in the LT3/4 progenitor and VA1/2 progenitor but not that of LT1/2 (Figure 2A). Kr continued to be detected in the FCs for LT1-4, VA1, and VA2 immediately after division and was detectable through stages 14 and 15 Beckett and Baylies 2007;Carrasco-Rando et al 2011), but declined in the LT1, LT3, and VA1 FCs by late stage 11 (Figure 2, B-D) Beckett and Baylies 2007;Carrasco-Rando et al 2011). Similarly, Mid was lost in the VA1 and LT3 FCs by stage 12 but, like Kr, was detectable in the FCs and the growing VA2 and LT4 muscles into stage 15 (Figure 2, E-G, Figure S2).…”
Section: Muscles Form Correct Attachments In Mid Mutantsmentioning
confidence: 94%
See 2 more Smart Citations
“…Or, by controlling the expression of the slouch gene, Ara and Caup specify the lateral transverse muscle fate. 13 Iro genes contribute to territorial growth in the eye and wing imaginal discs by generating organizing borders at the Keywords: cell proliferation, Drosophila, imaginal discs, Iroquois genes, tumor suppressor genes List of abbreviations and acronyms: ara, araucan; CBD, Cyclin Binding Domain; Cdk2, Cyclin-dependent kinase 2; caup, caupolican; HD, homeodomain; Iro, Iroquois; Irx, Iroquois-related genes; mirr, mirror; TALE, Three Amino acid Loop Extension; TSG, Tumor Suppressor Genes confrontation of Iro-expressing and nonexpressing cells (the dorso/ventral and the notum/wing hinge organizers, respectively. [7][8][9]14 ) In addition, the observation that clones of iro mutant cells in the eye disc are larger than wild-type clones suggested that Iro proteins played a role in the control of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%